Competitiveness of Georgian Commercial Banks in the Financial Market - Natia Gadelia (European Scientific Journal, ESJ, 2025)
This research explores the competitiveness of Georgian commercial banks, with a particular focus on their financial performance, market positioning, and the role of innovation in sustaining market leadership. A well-functioning banking sector is crucial for the financial stability of a country, as commercial banks play a central role in facilitating the flow of funds within the economy. Efficient banks help save time and resources for both depositors and borrowers. However, the failure of a bank can cause significant harm to both its clients and the broader financial system.The study aims to assess the competitiveness of Georgian commercial banks, identifying the factors and indicators that contribute to their success in the financial market. By focusing on key financial performance metrics, customer satisfaction, and investor confidence, this research evaluates how leading banks like JSC "TBC Bank" and JSC "Bank of Georgia" maintain their market positions through diverse services, innovative strategies, and effective market segmentation. Other banks, such as JSC "ProCredit Bank" and JSC "Credo Bank," are also analyzed for their unique appeal in the sector.The research addresses not only the financial indicators but also the importance of innovation and effective management in driving competitiveness. In the current globalized environment, banks must continuously adapt to technological advancements and develop risk management strategies to remain competitive. Therefore, this study also examines how innovations and modern trends, such as direct banking, impact the overall competitiveness of Georgian commercial banks.In conclusion, by analyzing both financial and non-financial factors, the research provides valuable insights into the key elements that determine the leadership and competitiveness of Georgian commercial banks in today’s financial market.